THE DEVELOPMENT OF STEM (SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS) BASED INQUIRY LEARNING PACKAGES TO TRAIN STUDENTS CRITICAL THINKING SKILL - Maya Fahrudatul Isdianti; Erman Erman; Harun Nasrudin (Universitas Negeri Surabaya, 2021)
This study aimed to develop STEM based inquiry learning packages on simple machines topics to train students critical thinking skill. The type of study is Research and Development (R&D) with 4D development model, which consists of defining, designing, developing and disseminating. Learning packages included syllabus, lesson plans, worksheets, handouts and tests of students critical thinking skill. The research subjects were 28 students of grade VIII in SMPN 1 Pamekasan who were obtained by purposive sampling technique. This research based on validity and practicy. Data were collected using validation sheets, teacher activity observation sheets and student activity observation sheets. The validity data was obtained based on the results of the mode assessment done by 3 validators by validation sheet. Descriptive data were analyzed quantitatively. The results of the 3 validators assessment obtained 4 for mode value which was very valid, and the average of reliabelity Cronbachs Alpha was 0,848 in the reliable category. The result of implementation learning is 92% and student activity is 88% with very good category. This showed that the development of STEM based inquiry learning packages was categorized as valid and reliable for use based validity and practicy.